VIOLÊNCIA ESCOLAR E PRÁTICAS RESTAURATIVAS: PROJETO CIDADANIA PARA TODOS - Ames, Maria A. C.; Hauser, Ester; Bach, Franciele M.; Silva, Susan L. d.; Kafczinski, Bruna A.; Poletto, Luana (Salão do Conhecimento, 2013)
Resumo